2019
DOI: 10.1371/journal.pone.0212657
|View full text |Cite
|
Sign up to set email alerts
|

Help-seeking behavior of Jimma university students with common mental disorders: A cross-sectional study

Abstract: Background Globally, the mental health help-seeking behavior of university students is reported to be poor; less than one-third of university students with common mental disorders (CMDs) report having sought help from formal sources. Failure to seek treatment is associated with prolonged disability and poor mental health outcomes, including suicide. In Ethiopia, little is known about the help-seeking behavior of university students for CMDs. Objective This study aimed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
46
9
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(62 citation statements)
references
References 57 publications
4
46
9
3
Order By: Relevance
“…The current finding is lower than what was reported in previous studies in Ethiopian universities [45,60]. The first possible justification for the difference might be data collection instrument being used to screen mental distress [45,60]. The second possible reason for the difference could be data collection time in which exam was approaching [60].…”
Section: Discussioncontrasting
confidence: 89%
See 2 more Smart Citations
“…The current finding is lower than what was reported in previous studies in Ethiopian universities [45,60]. The first possible justification for the difference might be data collection instrument being used to screen mental distress [45,60]. The second possible reason for the difference could be data collection time in which exam was approaching [60].…”
Section: Discussioncontrasting
confidence: 89%
“…The other explanation for the difference might be resulted from not using locally validated instrument [59]. The current finding is lower than what was reported in previous studies in Ethiopian universities [45,60]. The first possible justification for the difference might be data collection instrument being used to screen mental distress [45,60].…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…Previous studies reported various reasons for not receiving formal health service by undergraduate university students with mental distress [36,39,40]. For instance, a study which was conducted in St.…”
mentioning
confidence: 99%
“…Catherine University, US, reported the main reasons for not using university counseling center were receiving help from friends or family, preference for self-management, considering their problems as not serious enough, and thinking the problem would get better by itself [39]. In addition, commonly reported barriers to receive mental health service were lack of perceived need, being unaware of the existence of such services, fear of stigma, concerns about privacy, lack of time, skepticism about treatment effectiveness, socioeconomic problem [36], denial and not wanting to be labeled as "crazy" [40].…”
mentioning
confidence: 99%